Hybrid Learning in Pesantren: Integrating Digital Pedagogy and Islamic Values to Enhance 21st-Century Competencies - Sugito, Sugito (Tafkir: Interdisciplinary Journal of Islamic Education, 2024)
Education in Islamic boarding schools remains predominantly rooted in traditional models that demonstrate limited adaptability to contemporary technological innovations. At the same time, these institutions face the imperative to endure and evolve in order to fulfill their enduring educational mission. This study examines the innovation of hybrid learning methods in pesantren as a solution to the challenges faced by Islamic education in the digital era. The hybrid approach integrates traditional face-to-face instruction with structured, technology-based digital learning. This model offers increased flexibility, accessibility, and a more contextualized learning experience without relinquishing the Islamic values that define pesantren. Through a literature review and thematic analysis, the research reveals that the hybrid model enhances santri’s twenty-first-century competencies—such as digital literacy, collaboration, and problem-solving—while maintaining their religious character. Additionally, the study proposes a holistic framework for the implementation and evaluation of hybrid learning, encompassing cognitive, affective, psychomotor, and digital-ethical dimensions. Effective and sustainable realization of this innovation demands synergistic collaboration among government authorities, pesantren administrators, and educators.